2013
DOI: 10.1128/iai.00405-12
|View full text |Cite
|
Sign up to set email alerts
|

Increased Resistance to Staphylococcus aureus Endophthalmitis in BALB/c Mice: Fas Ligand Is Required for Resolution of Inflammation but Not for Bacterial Clearance

Abstract: FasL was recently shown be required for bacterial clearance in C57BL/6 mice that express the FasL.1 allotype. The FasL.2 allotype is expressed in BALB/c mice and exhibits increased binding affinity to and increased cytotoxic activity against Fas ؉ target cells. Therefore, we hypothesized that BALB/c mice would be more resistant to Staphylococcus aureus-induced endophthalmitis. To test this hypothesis, C57BL/6, BALB/c, and BALB(gld) mice received intravitreal injections of 2,500 CFU of S. aureus (RN6390). Clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…To determine the in vivo roles of TLR2 and MyD88 signaling in the pathogenesis of bacterial endophthalmitis, the eyes of WT (C57BL/6), TLR2 À/À , and MyD88 À/À mice were challenged by inoculation of S. aureus as described previously. 2,17,28 Disease severity, as measured by clinical score, showed a time-dependent progression. The average clinical score of TLR2 À/À mice did not differ significantly from that of WT mice, whereas MyD88 À/À mice had higher clinical scores at 1 day post infection (DPI).…”
Section: S Aureus Causes Increased Retinal Tissue Damage In Tlr2 à/àmentioning
confidence: 99%
See 2 more Smart Citations
“…To determine the in vivo roles of TLR2 and MyD88 signaling in the pathogenesis of bacterial endophthalmitis, the eyes of WT (C57BL/6), TLR2 À/À , and MyD88 À/À mice were challenged by inoculation of S. aureus as described previously. 2,17,28 Disease severity, as measured by clinical score, showed a time-dependent progression. The average clinical score of TLR2 À/À mice did not differ significantly from that of WT mice, whereas MyD88 À/À mice had higher clinical scores at 1 day post infection (DPI).…”
Section: S Aureus Causes Increased Retinal Tissue Damage In Tlr2 à/àmentioning
confidence: 99%
“…A Lower Dose of S. aureus Causes Endophthalmitis in TLR2 À/À and MyD88 À/À Mice Previous studies have shown that intravitreal injection of 500 CFU of S. aureus causes transient inflammation in WT mice; however, the bacteria are cleared by 3 DPI, and inflammation is resolved. 4,17,28 Having shown the increased susceptibility of TLR2 À/À and MyD88 À/À mice by using a dose of 5000 CFU/eye, we sought to determine whether 500 CFU/eye, a 10-fold lower dose could cause endophthalmitis in these KO mice. To this FIGURE 7.…”
Section: Cramp-deficient Mice Are More Susceptible To S Aureus Endopmentioning
confidence: 99%
See 1 more Smart Citation
“…However, S. aureus endophthalmitis in FasL-deficient knockout mice followed a much more aggressive course than infection in wild type background mice which were able to clear the infection (Engelbert and Gilmore, 2005). Sugi et al (2013) also reported that FasL was required for resolution of inflammation during experimental S. aureus endophthalmitis, but not for clearance of the bacteria.…”
Section: Experimental Models: Therapeutics and Virulencementioning
confidence: 99%
“…aureus remains largely unknown. We [68] and others [9, 10] have reported the different susceptibility to S . aureus in various inbred mouse strains.…”
Section: Introductionmentioning
confidence: 99%